AUP1 regulates lipid metabolism and induces lipid accumulation to accelerate the progression of renal clear cell carcinoma. Issue 8 (27th June 2022) - Chen, Chen; Zhao, Wei; Lu, Xingxing; Ma, Yunbo; Zhang, Peizhi; Wang, Zicheng; Cui, Zilian; Xia, Qinghua
Abstract: Lipid metabolic reprogramming is a prominent feature of clear cell renal cell carcinoma (ccRCC). Lipid accumulation affects cellular energy homeostasis, biofilm synthesis, lipid signal transduction, and phenotypic transformation in ccRCC. Herein, a prognostic‐related model was constructed, and the prognostic utility of AUP1, a lipid droplet–regulating very low–density lipoprotein assembly factor, in ccRCC was determined through multiparameter analysis. AUP1 expression was significantly higher in clinical samples than in normal tissues and was closely associated with the clinical stage. The inhibition of AUP1 expression impaired the proliferation, migration, and invasion of ACHN and A498 ccRCC cells in vitro and in vivo. RNA‐seq analysis revealed that AUP1 inhibition can significantly reduce the contents of intracellular triglyceride and cholesterol and regulate cell growth by cell cycle arrest, promoting apoptosis and reversing epithelial‐mesenchymal transition. AUP1 regulated the synthesis of cholesterol esters and fatty acids (FAs) in ccRCC cells by targeting sterol O‐acyltransferase 1 and partially promoted the progression of ccRCC. AUP1 also induced lipid accumulation in ccRCC by promoting the de novo synthesis of FAs (inhibiting protein kinase AMP‐activated catalytic subunit alpha 2), inhibiting the rate‐limiting enzyme of FA β oxidation (carnitine palmitoyltransferase 1A), regulating the key enzyme of lipolysis (monoglyceride lipase, MGLL), and inhibiting the lipid transporter StAR‐related lipid transfer domain containing 5 (STARD5). However, it did not affect the intracellular cholesterol synthesis pathway. The differential expression and prognostic significance of MGLL and STARD5 in ccRCC should be further studied. AUP1 may serve as a new and effective potential target and prognostic marker for ccRCC. Abstract : We used a publicly available database to construct a prognostic risk model for ccRCC, and through subsequent verification and multi‐parameter analysis, we screened and extracted that AUP1 is significantly highly expressed in ccRCC and is closely related to the clinical prognosis. Combined with RNA‐seq, in vivo, in vitro experiments and clinical samples, we revealed that AUP1 induced lipid accumulation in ccRCC by mediating fatty acid and cholesterol pathways, and realized lipid reprogramming, thus promoting the progression of ccRCC.